Cover Image, Volume 237, Number 8, August 2022. Issue 8 (13th August 2022) - Pereira, Jéssica; Dias, Raphael; Ramos, Isabela
Abstract : Inside Front Cover : The cover image is based on the Research Article Knockdown of E1‐ and E2‐ubiquitin enzymes triggers defective chorion biogenesis and modulation of autophagy‐related genes in the follicle cells of the vector Rhodnius prolixus by Jéssica Pereira et al., https://doi.org/10.1002/jcp.30806 .